Calling Baumol: What telephones can tell us about the allocation of entrepreneurial talent in the face of radical institutional changes - Sorgner, Alina; Wyrwich, Michael (Journal of Business Venturing, 2022)
In his seminal contribution, Baumol (1990) proposes that the direction of entrepreneurial effort towards its productive (e.g., start-up activity) or unproductive (e.g., rent-seeking) use in a society depends on institutions or the “rules of the game”. We focus on an important micro-foundation of Baumol's theory namely that certain individuals change the direction of entrepreneurial efforts with institutional change. Our research contrasts with previous work on the role of institutions, which mostly focuses on the aggregate macro-level, while not observing individual behavior. We analyze who decides to start a venture in East Germany after the fall of the Berlin Wall and find that many individuals who demonstrated commitment to the anti-entrepreneurial communist regime in the GDR were active in launching new ventures soon after German re-unification. We argue that commitment to communism among post-communist entrepreneurs reflects rent-seeking. Once institutions change radically, entrepreneurial efforts are directed towards start-up activity. We rely on the German Socio-Economic Panel Study (SOEP) that includes information on whether East German respondents had a telephone before German re-unification, which was one of the most sought-after rewards for commitment to the regime. We find that telephone owners had a higher propensity of becoming successful firm founders. Telephone owners were also more likely to have an entrepreneurship-prone personality profile and value orientation. Our results confirm Baumol's theory and suggest that alertness to entrepreneurial arbitrage opportunities is guiding the redirection of entrepreneurial effort in the face of drastic institutional change. There is a large body of literature on the effect of institutions on entrepreneurship. A good share of this literature is rooted in the seminal contribution by Baumol (1990) who argues that the shape of institutions determines whether people direct entrepreneurial effort to productive, unproductive or destructive entrepreneurial activities. Despite the fact that Baumol‘s main argument is at the individual micro-level, most of the literature focuses only on the macro-level implications of his theory. In contrast to most previous studies, we are not focusing on the aggregate level of entrepreneurship but explore the micro-foundations of Baumol's theory and analyze how (drastic) institutional change affects the entrepreneurial choice at the individual level. In our discussion of Baumol's work, we also introduce Kirzner's concept of individual alertness to arbitrage opportunities which he originally formulated for market economies. We extend Kirzner's insights on the role of alertness to other institutional contexts (e.g., socialism) and forms of arbitrage (e.g., engagement in socialist organizations) other than start-up activity, and highlight the role of institutional change in shaping processes of opportunity formation. It is important to understand how individuals allocate their entrepreneurial effort in times of major historical shocks and institutional changes for several reasons. First, since entrepreneurship is an important driver of economic growth and development, it is crucial to understand how institutional change affects entrepreneurial behavior at the individual level for designing policy measures targeted at increasing the entrepreneurial propensity of people. Second, the share of people with an entrepreneurial talent in a society is an enormous resource to cope with socio-economic change. Third, it is also important to understand the micro-foundations of Baumol's work as vast empirical evidence on the impact of institutions on entrepreneurial activities that is available at the macro-level relies on the validity of the micro-foundations. We find that people who demonstrated commitment to one of the most anti-entrepreneurial institutional regimes in history—communism—were more likely to start a firm after transition to a market economy. Our analysis is based on the case of East Germany that saw a sudden shift from an anti-entrepreneurial communist regime that did not reward start-up activities towards an entrepreneurship-facilitating market economy after the fall of the Berlin Wall. Those people who were actively committed to the regime as evidenced by material rewards obtained in the GDR were more likely to become (successful) self-employed after the fall of the Berlin Wall. We also observe that people with an entrepreneurship-prone personality profile and those who put a strong emphasis on entrepreneurial values were more likely to have obtained material rewards in communism that indicate a strong commitment to the system. We argue that applying and extending Baumol's and also Kirzner's ideas helps understanding this puzzling phenomenon. In essence, regime commitment can be seen as a form of rent-seeking activity, which is a classic example of unproductive entrepreneurial activity discussed by Baumol. Rent-seeking in the context of communism could be expressed, for example, in enthusiastic engagement in public organizations (e.g., party councils, youth organizations, state-owned enterprises) in exchange for specific material rewards. Their pronounced alertness to new arbitrage opportunities may have enabled these same individuals to switch to start-up activity once this option became available to them and if it was more profitable than rent-seeking. We contribute to the literature by supporting the idea that the institutional framework conditions determine the type of entrepreneurial activity to which entrepreneurially talented people devote their efforts. So far, this claim found support mainly in aggregated macro-level data. Another important insight from our analysis is that entrepreneurs are flexible and agile economic agents who are alert to arbitrage opportunities and able to promptly adapt themselves to even radical changes, such as the shock transition from a socialist command economy to a market economy. Alertness to opportunities in a market economy context could hardly be learned in an anti-entrepreneurial context. Hence, an immediate re-allocation of entrepreneurial efforts indicates that alertness to arbitrage opportunities emerging in a market economy does not necessarily require experience in a market economy context. Our assessment also suggests that institutional change is shaping subjective processes of opportunity formation. Hence, the debate on whether opportunities are ‘out there’ or they have to be created should take into consideration how institutions and institutional change set the boundaries for opportunities. In particular, identifying and pursuing new opportunities brought about by institutional change could represent a specific form of “entrepreneurship talent.”